2015
DOI: 10.1542/hpeds.2014-0094
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Vs Magnetic Resonance Imaging for Identifying Acute Lesions in Pediatric Traumatic Brain Injury

Abstract: Compared with CT, MRI identified significantly more intraparenchymal lesions in pediatric TBI, particularly in children with abusive head trauma. The prognostic value of identification of intraparenchymal lesions by MRI is unknown but warrants additional inquiry. Risks and benefits from early MRI (including sedation, time, and lack of radiation exposure) compared with CT should be weighed by clinicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 30 publications
0
23
0
4
Order By: Relevance
“…Buttram et al [12] debate the merits of using CAT scan (CT) versus MRI to image children who may be victims of AHT. The studies are complementary, with 3D reconstruction of CT scan providing information about skull fractures and MRI often yielding more information about parenchymal injury.…”
Section: Abusive Head Traumamentioning
confidence: 99%
“…Buttram et al [12] debate the merits of using CAT scan (CT) versus MRI to image children who may be victims of AHT. The studies are complementary, with 3D reconstruction of CT scan providing information about skull fractures and MRI often yielding more information about parenchymal injury.…”
Section: Abusive Head Traumamentioning
confidence: 99%
“…33,34 Though CT remains the diagnostic standard in acute neuroimaging, where available MRI may provide additional clinically relevant information, in addition to that required for immediate surgical decision making or acute management decisions such as hospital admission. 35 In particular, intraparenchymal lesions, such as contusions, ischemia, and traumatic or diffuse axonal injury, and posterior fossa lesions may not be easily detectable on CT imaging but evident with MRI. Such lesions not only correlate with outcomes but may also impact clinical management decisions.…”
Section: Acute and Serial Imaging-evolving Goalsmentioning
confidence: 99%
“…7 Several studies have shown that conventional MRI has equal or higher sensitivity for detection of intracranial hemorrhage and intraparenchymal injury. 6,[8][9][10][11] A retrospective study of 105 children with TBI reported that conventional MRI detected more than twice as many intraparenchymal lesions compared with CT. 11 In addition, Huisman et al reported that diffusion weighted imaging (DWI) identifies the largest number of TAI lesions fast-spin echo (FSE) T2weighted (T2WI), fluid-attenuated inversion recovery (FLAIR), and T2 Ã gradient-recall echo (GRE) sequences. 12 DWI was also shown to contribute to predictive models of injury outcomes.…”
Section: The Evolving Role Of Mri In Acute Pediatric Tbimentioning
confidence: 99%